Band Gaps and Optical Spectra of Chlorographene, Fluorographene and Graphane from G0W0, GW0 and GW Calculations on Top of PBE and HSE06 Orbitals - Karlický, František; Otyepka, Michal (Journal of chemical theory and computation, 2013)
The band structures of three graphene derivatives (chlorographene, fluorographene, and graphane) were analyzed at three levels of many-body GW theory (G0W0, GW0, and GW) constructed over GGA (PBE) and screened hybrid HSE06 orbitals. DFT band gap values obtained with the HSE06 functional were notably larger than those from PBE calculations but were significantly lower than band gaps from all GW calculations. On the other hand, all GW-type calculations gave similar band gaps despite some differences in band structures. The band gap (4.9 eV at the highest GW-HSE06 level) was predicted to be smaller than that of fluorographene (8.3 eV) or graphane (6.2 eV). However, chlorographene can be considered a wide-band gap insulator analogous to fluorographene and graphane. Using the Bethe-Salpeter equation, optical absorptions of graphene derivatives were found to be at significantly lower energies due to large binding energies of excitons (1.3, 1.9, and 1.5 eV for chlorographene, fluorographene, and graphane, respectively). Point defects lowered band gaps and absorption energies. Taking into account the low concentration of defects in this type of material, their effect on the discussed electronic properties was rather small.